8x+2=-6+3x+23

Simple and best practice solution for 8x+2=-6+3x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+2=-6+3x+23 equation:


Simplifying
8x + 2 = -6 + 3x + 23

Reorder the terms:
2 + 8x = -6 + 3x + 23

Reorder the terms:
2 + 8x = -6 + 23 + 3x

Combine like terms: -6 + 23 = 17
2 + 8x = 17 + 3x

Solving
2 + 8x = 17 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
2 + 8x + -3x = 17 + 3x + -3x

Combine like terms: 8x + -3x = 5x
2 + 5x = 17 + 3x + -3x

Combine like terms: 3x + -3x = 0
2 + 5x = 17 + 0
2 + 5x = 17

Add '-2' to each side of the equation.
2 + -2 + 5x = 17 + -2

Combine like terms: 2 + -2 = 0
0 + 5x = 17 + -2
5x = 17 + -2

Combine like terms: 17 + -2 = 15
5x = 15

Divide each side by '5'.
x = 3

Simplifying
x = 3

See similar equations:

| x^4+2x^2-36=0 | | (4x+5y)+(x+7y)= | | 1.5-0.04x=1.5 | | (x^2)-(2x)+(2)=0 | | 8+2=-6+3x+23 | | 5x+11y=-13 | | 7(v+3)-4v=27 | | 3x-9=12x-13 | | (X^2)-216=0 | | x^2-8x-42=-2x-2 | | -60p+260=90p-40 | | X(-2)=-64 | | s+0.25s+20=55 | | -5p^2+15000p-1750000=0 | | 9-y=12 | | x^2+5x-11=-6x+1 | | 7=1+3a | | y=-4.905x^2+5x+22 | | 12=-3t | | x^2+36x+225=0 | | 3+ln(x+2)=8 | | -8v=-40 | | x+2x+(x+15)=115 | | 125m-100m+45,000=43,650-200m | | 3x-9=3(2x-4) | | -9x=-135 | | 375=45+60 | | y^2-8y+17=x | | 12=16x+12 | | 12x+26=8x-11 | | 0.0003X-2.3245Y=X+Y-3.2543 | | -11+2n+2-6=-8-5n |

Equations solver categories